2014
DOI: 10.1128/aem.01525-14
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Diversity of Tailed Phages, Eukaryote-Associated Viruses, and Virophage-Like Elements in the Metaviromes of Antarctic Soils

Abstract: dThe metaviromes of two distinct Antarctic hyperarid desert soil communities have been characterized. Hypolithic communities, cyanobacterium-dominated assemblages situated on the ventral surfaces of quartz pebbles embedded in the desert pavement, showed higher virus diversity than surface soils, which correlated with previous bacterial community studies. Prokaryotic viruses (i.e., phages) represented the largest viral component (particularly Mycobacterium phages) in both habitats, with an identical hierarchica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 47 publications
13
85
0
Order By: Relevance
“…3). This is consistent with a recent study that identified greatest abundance of Myoviridae (21 %) and Siphoviridae (53 %) in Antarctic hypoliths (Zablocki et al 2014). The Levriviridae are found worldwide, and isolated strains infect gram-negative bacteria (Hulo et al 2011).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…3). This is consistent with a recent study that identified greatest abundance of Myoviridae (21 %) and Siphoviridae (53 %) in Antarctic hypoliths (Zablocki et al 2014). The Levriviridae are found worldwide, and isolated strains infect gram-negative bacteria (Hulo et al 2011).…”
Section: Resultssupporting
confidence: 80%
“…The nearubiquity of vial signature recovery in this study is consistent with theory regarding phage distribution in natural environments (Breitbart and Rohwer 2005). A recent study of the Antarctic hypolithic metavirome indicated that a range of microbial physiological pathways may also be encoded Error bars represent standard deviation of the mean for three independent GeoChip replicates, where these are not visible standard deviation is less than the minimum scale increment within phage genomes, in addition to virulence, disease and defence functions (Zablocki et al 2014). Thus, high viral loads in microbial communities in extreme environments may also reflect, in part, acquisition of favourable auxiliary metabolism genes (Roossinck 2011) and may even increase bacterial diversity by selecting for multiple resistance traits (Koskella and Brockhurst 2014).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Such genome data may be crucial in revealing mechanistic insights of polar cyanobacterial isolates as has been done very recently with other phyla Ferreras et al 2014;Guerrero et al 2014;Ronca et al 2015). There is also a general lack of publicly available cyanobacterial virome data, which may lead to poor representation and potential underestimation of cyanophages in Antarctic environments (Zablocki et al 2014). This deficit negatively affects our understanding of intra-and interspecies interactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few studies have assessed the diversity of viruses in cold environments, let alone their functional roles. Of these published studies on polar habitats, mostly focus on lacustrine systems [54,55] with only very limited surveys of polar edaphic metaviromes [40,56]. The latter suggests that viruses in cold soil environments are highly diverse but are typically dominated by Mycobacterium phages [56].…”
Section: Microbial Diversity In Cold Environmentsmentioning
confidence: 99%